Ag Nanorods-Based Surface-Enhanced Raman Scattering: Synthesis, Quantitative Analysis Strategies, and Applications - Zou, Sumeng; Ma, Lingwei; Li, Jianghao; Liu, Yuehua; Zhao, Dongliang; Zhang, Zhengjun (Frontiers in Chemistry, 2019)
Surface-Enhanced Raman Scattering (SERS) is a powerful technology that provides abundant chemical fingerprint information with advantages of high sensitivity and time-saving. Advancements in SERS substrates fabrication allow Ag nanorods (AgNRs) possess superior sensitivity, high uniformity, and excellent reproducibility. To further promote AgNRs as a promising SERS substrates candidate to a broader application scope, oxides were integrated with AgNRs by virtue of their unique properties which endows the AgNRs-oxide hybrid with high stability and recyclability. Aside from SERS substrates fabrication, significant developments in quantitative analysis strategies offer enormous approaches to minimize influence resulted from variations of measuring conditions and to provide a reasonable data analysis approach. In this review, we discuss various fabrication approaches for AgNRs and AgNRs-oxide hybrids to achieve efficient SERS platform. Then, we introduce three types of strategies which are commonly employed in chemical quantitative analysis to reach a reliable result. Further, we highlight SERS applications including food safety, environment safety, biosensing, and vapor sensing, demonstrating the potential of SERS as a powerful and promising technique. Finally, we conclude with the current changes and future prospects towards efficient SERS manipulation for a broader real-world applications.